A preliminary survey of the terrestrial arthropods of the Rosenthal Islands, Antarctica - Gantz, J D; Spacht, Drew E; Lee, Richard E (Polar Research, 2018)
The Rosenthal Islands lie along the western edge of the Antarctic Peninsula. They are largely inaccessible and the few research projects in the area have focused on seabird colonies, so nothing has been known about the arthropod fauna on these islands. We conducted a preliminary survey of the arthropods associated with large penguin colonies. We identified two species of Collembola (Cryptopygus antarcticus and Friesea grisea), four species of mites (Alaskozetes antarcticus, Hydrogamasellus racovitzai, Tectopenthalodes villosus and Rhagidia sp.) and one insect (Belgica antarctica). The mite A. antarcticus and the collembolan C. antarcticus were common in large aggregations at our collecting sites and were occasionally observed on the surface of penguin guano without vegetative cover. The insect, a chironomid midge, was less common and found only in vegetated areas.
Keywords: Antarktis; biologi; fauna; leddyr; midder; pingviner; zoologi

Mites collected in Heimefrontfjella and Vestfjella (Dronning Maud Land, Antarctica) - Thor, Göran (Fauna norvegica. Serie B, 1996)
Keywords: Dronning Maud Land; dyr; midder; zoologi

Notes on the ecology and physiology of the Antarctic oribatid mite Maudheimia wilsoni - Sømme, Lauritz; Strømme, Alexander; Zachariassen, Karl Erik (Polar Research, 1993)
The oribatid mite Maudheimia wilsoni Dalenius was found to be numerous on the underside of stones at Jutulsessen (72-degrees-S, 3-degrees-E) in Dronning Maud Land, Antarctica. Daily temperature fluctuations of the microhabitat from as high as 19-degrees-C and to as low as -17-degrees-C were observed during the austral summer. Optimal activity of the mites occurred at 10-degrees-C. Even in January the mean supercooling point of adult mites was as low as - 30.8 +/- 4.7-degrees-C. Haemolymph osmolality ranged from 500 to 800 mOsmol and thermal hystersis freezing points from -4.7 to - 6.1-degrees-C. Adult mites had a mean water content of 43.6% and a water loss rate of 0.12 mug h-1 at 15-degrees-C and 10% relative humidity.
Keywords: Dronning Maud Land; NARE 1989/90; entomologi; midder; miter; virvelløse dyr; zoologi; økofysiologi; økologi

Ecophysiological adaptations in mites and collembolans in Dronning Maud Land - Strømme, Alexander (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; midder; miter; virvelløse dyr; zoologi; økofysiologi

Terrestrial arthropods of Bouvetøya - Sømme, Lauritz (Polar Research, 1986)
Keywords: Bouvetøya; ekspedisjoner; forskning; midder; miter; virvelløse dyr

Cold Hardiness of Terrestrial Mites at Signy Island, Maritime Antarctic - Block, William; Sømme, Lauritz (Oikos, 1982)
The cold hardiness of four species was studied in respect of supercooling ability, cryoprotective substances, chill-coma temperatures and survival under anaerobiosis. The effects of low temperature acclimation and starvation on cold hardiness were examined experimentally. (2) Mean supercooling points of field animals ranged from -6.1° to -28.8°C during Jan-Mar 1980. In Nanorchestes antarcticus (Strandtmann) and Alaskozetes antarcticus (Michael), a bimodal distribution of individual supercooling points occurred with the low group (LG) consisting of animals without gut nucleators. In Stereotydeus villosus (Trouessart) and Gamasellus racovitzai (Trouessart) only a high group (HG) was present in the supercooling-point distributions. (3) In all species, except the predatory G. racovitzai, starvation combined with low temperature exposure for various time periods lowered the mean supercooling point. This was associated with increased concentrations of glycerol in the body fluid. Glucose, ribitol and mannitol together with straight chain hydrocarbons were also detected in the extracts by GLC techniques. (4) Chill-coma temperatures varied from -4.5° to -8.0°C. (5) Under anoxia at 0°C, survival of A. antarcticus was greater than that of G. racovitzai, with the later nymphal stages being slightly more resistant than adults.
Keywords: Antarktis; Sør-Orknøyene; entomologi; kuldetoleranse; midder; miter; virvelløse dyr

Cold tolerance of alpine, Arctic, and Antarctic Collembola and mites - Sømme, Lauritz (Cryobiology, 1981)
Because of their dominant role in the fauna of alpine, Arctic and Antarctic locations Collembola and mites are of particular interest regarding adaptations to low temperatures. No freezing-tolerant species have been found in these groups of terrestrial arthropods, and it appears that all species depend entirely on supercooling to survive the lower temperatures of their habitats. While summer animals have high supercooling points, an increase in supercooling ability occurs during autumn and early winter, and can be explained as a two-step process. Initially gut content has to be eliminated to avoid heterogeneous nucleation at high subzero temperatures due to foreign nucleating agents. Second, supercooling is further enhanced through accumulation of glycerol or other lowmolecular cryoprotective substances. Further studies are needed on the ability of such animals to avoid inoculative freezing in their microhabitats.
Keywords: Antarktis; entomologi; kuldetoleranse; midder; miter; virvelløse dyr; zoologi

Notes on the cold-hardiness of prostigmate mites from Vestfjella, Dronning Maud Land - Sømme, Lauritz (Norwegian Journal of Entomology, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; kuldetoleranse; midder; miter; virvelløse dyr; zoologi

Prostigmate mites (Acari, Prostigmata) from Sverdrupfjella, Dronning Maud Land, with description of four new species - Strandtmann, Russell W; Sømme, Lauritz (Norwegian Journal of Entomology, 1977)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; midder; miter; virvelløse dyr; zoologi